Semar puppet counseling model - Habsy, Bakhrudin All (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Puppet as the original local wisdom has a great role in the character building and giving a good example of how to behave, puppet is also the source or guidance of how to behave well. One of the figures in puppet that has strong characteristic as the leader, protector, patron, and also the guide for ksatria in taking the decision is Semar. Semar has the perfection ethic of Javanese person and raise as the core of the soul of Javanese people. Semar’s wisdom can be applied in the development of multi culture Counseling for Counselor and multi culture Counseling characteristic. The characteristic of multi cultural based Counselor are: (1) Prudent, (2) Helper, (3) Motivator, (4) Democratic, (5) Fair, (6)Associating, (7) Sustains on the objectives, (8) Responsible, (9) Teaching, (10) Wholeheartedly, (11) Well mannered, (12) Sincere, (13) Honest, (14) Faithful, (15) Unpretentious (16) Not an anti critical, (17) Able to keep secret, and (18) Positive thinking. The application of Counseling based on the Semar’s characters is offered to develop the practice of multi cultural Counseling for the Counselors, it called puppet semar counseling model.